Implementation Of The Concept Of Tafaqquh Fī Al Dīn In The Context Of Education At The Persatuan Islam Islamic Boarding School 27 Situaksan City Of Bandung - Acep Saefuddin; Didin Nurul Rosidin; Adang Djumhur (Journal of Pedagogi, 2024)
The concept of Tafaqquh Fī al-Dīn holds significant importance in Islamic education, emphasizing a deep understanding of religion that is applicable to everyday life. Islamic boarding schools pesantren play a crucial role in applying this concept, yet face major challenges in balancing tradition with modern demands. This study investigates the implementation of Tafaqquh Fī al-Dīn at Pesantren Persatuan Islam 27 Situaksan, Bandung, focusing on the understanding of the asatidz (teachers), its application within the school, student responses, challenges encountered, and its impact on the formation of Islamic character and knowledge. Previous research (Hefner, 2009; Steenbrink, 1986) highlights the dilemma faced by pesantren in maintaining tradition while embracing modern innovations. Using a descriptive qualitative approach, with interviews, observation, and document analysis, this study reveals that while the asatidz understand Tafaqquh Fī al-Dīn, its implementation is hindered by institutional factors, limited infrastructure, and lack of skilled human resources, aligning with Ahmad’s (2017) findings on educational modernization. Although students respond positively, time and physical limitations pose challenges. To sustain relevance in the modern era, further innovations are necessary, as proposed by Azra (2015) in his study on the transformation of Islamic education in Indonesia.